Thermodynamics and Mechanism of Molecular Association of Butyrophenones and Related Molecules with Iodine — Part II - Saksena, A.R. (Asian Journal of Chemistry, 2010)
Dielectric constant measurements have been made for the various compositions of butyrophenones-iodine system in benzene at a radio frequency of 1 MHz at 30ºC and 40ºC. Precise density determination or donor-acceptor solutions has been made by a calibrated double stem pyknometer. Kinetic and thermodynamic parameters have been evaluated to interpret 1 : 1 molecular association. UV spectra has been used to support the mechanism. A correlation has been discussed in the light of above studies.